2011
DOI: 10.1371/journal.pntd.0001217
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Population Structures of Two Vectors of African Trypanosomoses in Burkina Faso: Consequences for Control

Abstract: BackgroundAfrican animal trypanosomosis is a major obstacle to the development of more efficient and sustainable livestock production systems in West Africa. Riverine tsetse species such as Glossina palpalis gambiensis Vanderplank and Glossina tachinoides Westwood are the major vectors. A wide variety of control tactics is available to manage these vectors, but their removal will in most cases only be sustainable if the control effort is targeting an entire tsetse population within a circumscribed area.Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 56 publications
4
37
1
Order By: Relevance
“…G. p. palpalis in this Cameroon forest area then forms relatively large panmictic populations, as compared to other works on G. palpalis populations Kone et al, 2011;Ravel et al, 2007;Solano et al, 2009Solano et al, , 2010b, with substantial dispersal between neighboring subpopulations, suggesting ''suppression'' as the best strategy to be adopted for anti-vector campaigns. The establishment of physical barriers is of a great importance whatever the anti-vector strategy in this forest context, because of the ubiquity of the tsetse flies here, and their dispersal capacity.…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…G. p. palpalis in this Cameroon forest area then forms relatively large panmictic populations, as compared to other works on G. palpalis populations Kone et al, 2011;Ravel et al, 2007;Solano et al, 2009Solano et al, , 2010b, with substantial dispersal between neighboring subpopulations, suggesting ''suppression'' as the best strategy to be adopted for anti-vector campaigns. The establishment of physical barriers is of a great importance whatever the anti-vector strategy in this forest context, because of the ubiquity of the tsetse flies here, and their dispersal capacity.…”
Section: Resultssupporting
confidence: 47%
“…In population genetics studies of tsetse flies using microsatellite markers, heterozygote deficits have frequently been reported Kone et al, 2010Kone et al, , 2011Mélachio et al, 2011;Ravel et al, 2007;Solano et al, 2000Solano et al, , 2009. In these studies, the use of several methods of analysis have shown that the Wahlund effect, the presence of null alleles and of short alleles dominance were probable sources of the artificial heterozygote deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most populations (24 out of 37) were specifically sampled for this study using biconical traps (1-11 traps by site). Traps were set at ∼100-m intervals for a maximum period of 1 wk and with a maximum distance of 1 km between first and last traps (10). We also included in the analysis 13 previously sampled populations (9, 10).…”
Section: Methodsmentioning
confidence: 99%